A Trilogy of Islamic Teachings in Sufism: Trilogi Ajaran Islam dalam Tasawuf - Arifah Salastiani Intan Intan (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2022)
ABSTRACT Every adherent of Islam knows for sure that Islam (al-Islam) is not valid without faith (al-Iman), and faith is imperfect without Ihsan (al-Ihsan). On the other hand, Ihsan is not possible without faith, nor is faith possible without Islamic initials. In further studies by experts, the meanings of the three terms are interrelated, even overlapping, so each contains the importance of the other two terms. In faith, there is Islam and Ihsan; in Islam, there is faith and Ihsan; in Ihsan, there is faith and Islam. From this perspective, we see faith, Islam, and Ihsan as a trilogy of divine teachings. Keywords: âqîdah, shariah, fiqh, ihsân, sufism ABSTRAK Setiap pemeluk Islam mengetahui dengan pasti bahwa Islam (al-Islam) tidak absah tanpa Iman (al-Iman), dan iman tidak dapat sempurna tanpa Ihsan (al-Ihsan). Sebaliknya, Ihsan adalah mustahil tanpa Iman, dan Iman juga tidak mungkin tanpa inisial Islam. Dalam telaah lebih lanjut oleh para ahli, lanjut oleh para ahli, ternyata pengertian antara ketiga istilah itu terkait satu dengan yang lain, bahkan tumpang tindih sehingga setiap satu dari ketiga istilah itu mengandung makna dua istilah yang lainnya. Dalam Iman terdapat Islam dan Ihsan, dalam Islam terdapat Iman dan Ihsan, dan dalam Ihsan terdapat Iman dan Islam. Dari sudut pengertian inilah kita melihat Iman, Islam dan Ihsan sebagai trilogi ajaran Ilahi.